And in the Evening She's a Singer with the Band : Second Jobs, Plight or Pleasure? - René Böheim; Mark P. Taylor (Institute for the Study of Labor (IZA), 2004)
We describe the dynamics of second job holding in Britain during the 1990s using panel data from the British Household Panel Survey. Our results show that second job holding is surprisingly persistent over time – about 10% of workers have a second job at any point in time while two thirds of second job holders remain in second jobs for at least two consecutive years. We find that negative financial shocks trigger second job holding, and that second jobs are not a measure to smooth labour supply over time. Heterogeneous main job characteristics are more important than hours constraints in determining second job holding.
Keywords: J6; J2; 330; second job; labour supply; BHPS; Nebentätigkeit; Arbeitsangebot; Schätzung; Grossbritannien